Jaklitera sebagai Pemenuhan Kebutuhan Informasi Masyarakat Pada Layanan Peminjaman Daring - Amaranti, Farah; Edwin Rizal; Rully Khairul Anwar (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2025)
This study explores the role of Jaklitera, a digital library application developed by the Jakarta Provincial Government, in fulfilling the informational needs of urban citizens through online borrowing services. Using a qualitative-descriptive approach supported by narrative observation, interviews, documentation, and literature review, the research investigates how Jaklitera adapts its system design, content provision, and user interface to the expectations of diverse library users. The findings show that Jaklitera not only enhances access to e-books, e-journals, and digital documents but also acts as a catalyst for building a responsive digital literacy ecosystem. However, several challenges remain, including gaps in user satisfaction, limited personalization, digital inequality, lack of interoperability across institutions, and the absence of formal operational standards. The study reveals that the effectiveness of Jaklitera lies in its ability to align technological features with human behavior, social inclusion, and evolving information needs. Theoretical insights drawn from the Technology Acceptance Model (TAM), Information-Seeking Behavior, and Public Value Theory frame Jaklitera as a public digital space that blends infrastructure with civic engagement. This research contributes to the discourse on library digital transformation by proposing a framework for developing user-centered, adaptive, and socially impactful digital library systems in Indonesia and beyond. Contribution: This study offers actionable recommendations and a conceptual framework for the future development of digital libraries, contributing both to academic literature and practical policy-making in the field of digital information services.